Legal Protection for Underage E-Sports Athletes in Employment Contracts within the E-Sports Industry under Labor Law - Bagus Trie Ramandha Hentrisman; Ratu Mawar Kartina; Henda Henda; Harmono Harmono (Journal of Legal and Cultural Analytics, 2026)
The rapid development of the e-sport industry in Indonesia has given rise to a new phenomenon involving underage athletes in contractual relationships with professional e-sport organizations. This study examines the legal protection afforded to underage e-sport athletes under Law Number 13 of 2003 concerning Manpower as amended by Law Number 11 of 2020 concerning Job Creation, while also analyzing the legal consequences arising from the placement of underage athletes within e-sport organizations, particularly the provisions of Articles 68–74 which prohibit the employment of children in heavy, hazardous, or work exceeding the minimum age limit. This research employs a normative juridical method with statutory and conceptual approaches, supported by library research encompassing primary, secondary, and tertiary legal materials. The findings reveal significant normative gaps in Indonesian labor regulations, wherein existing provisions have not comprehensively accommodated the distinctive characteristics of the e-sport industry as a digital economic sector. Employment contracts applied within the e-sport industry frequently fail to satisfy the legal capacity requirements prescribed under civil law and have not adequately guaranteed the fundamental rights of child athletes, including limitations on working hours, the right to education, and social security entitlements. This study recommends the establishment of specific regulations that are responsive to the dynamics of the e-sport industry in order to achieve legal certainty and comprehensive protection for child athletes as vulnerable legal subjects.